The Role of Artificial Intelligence in Supply Chain Management Transformation Economic and Business Implications - Syaifullah, Syaifullah (Journal of Economic Growth and Development Review, 2025)
This study explores the economic and business implications of implementing artificial intelligence (AI) in supply chain management. Using a mixed-methods approach that combines in-depth case studies of eight multinational companies, a survey of 312 supply chain professionals from 23 countries, and a panel data analysis of 128 companies over a five-year period (2018-2023), the study identifies four key dimensions of AI-driven economic transformation. The results show that AI implementation results in operational cost restructuring with an average reduction of 24% after 36 months, predictive efficiency improvements with forecast accuracy increasing by 37.8%, workforce reconfiguration with a shift from routine operational positions (-18.7%) to highly technical and analytical positions (+24.3%), and business model transformation with the emergence of AI-powered services that have 42.7% higher profit margins than traditional businesses. These findings illustrate a fundamental shift in the supply chain economy, where value comes not only from cost efficiency but also from increased resilience, workforce productivity, and the creation of new value propositions. This research contributes to a more comprehensive understanding of how digital transformation is changing the economic and business landscape in the context of global supply chains, with important implications for corporate strategy, employment policy, and competition regulation.